Bioactivity and hemolysis test of hydroxyapatite/zirconia composites (HAp/ZrO2-8Y2O3) for bone implants - Santillana-Marín, R. A.; Múzquiz-Ramos, E. M.; García-Cerda, L. A.; Cruz-Ortíz, B. R. (Revista Mexicana de Ingenieria Biomedica, 2018)
The synthesis of hydroxyapatite/zirconia composites (HAp/ZrO2-8Y2O3) is presented, using the liquid mixing me-thod based on the Pechini method, whose innovation lies in the simultaneous synthesis of both phases with uni-form distribution, although it has the limitation of the cations interactions, favoring the formation of secondary phases if the variables are not controlled. The obtained materials were formed into discs of 1 cm in diameter and treated at 1400 °C, and then characterized by infrared spectrometry (FTIR-ATR) and X-ray diffraction (XRD). The bioactivity tests were carried by the immersion method in simulated body fluid for 21 days and characterized by scanning electron microscopy (SEM) and X-ray photoelectron spectrometry (XPS). The hemolysis tests were based on the ASTM F 756-00 standard. After the immersion, the presence of hydroxyapatite crystals on the surface of the composite was observed; in addition, the XPS analyzes show energy signals for the elements of calcium and phos-phorus. Regarding the hemolysis tests, degrees of cytotoxicity were observed below 3%, it is inferred that they are hemocompatible, although more biocompatibility studies are required for biomedical application.